The Teachers’ Strategies In Teaching English Vocabulary At SMP N 6 Kota Jambi Academic Year 2017/2018 - Nurhayati . (Universitas Batanghari Jambi, 2018)
Abstract The Teachers’ Strategies In Teaching English Vocabulary At SMPN 6 Kota Jambi Academic Years 2018/2019.This research aims to know about what strategies are used by English teachers in teaching English vocabulary at SMPN 6 Kota Jambi. The purpose of this research is to find out the strategies of English teachers at SMPN 6 Kota Jambi in teaching English vocabulary. The method used in this research is qualitative methods. The setting of this research at SMPN 6 Kota Jambi, because the researcher recognize the teachers there especially English teachers. The subject of the research are all English teachers as a research subject. The data are collected through interview sheet. Based on the data analysis, the researcher find some strategies in teaching English Vocabulary, namely self-defining context, identifying picture, and antonym. The finding of this research from interview result is different teachers’strategies when teaching in the class. The conclusion is some strategies of teaching English vocabulary is very useful for teachers when teaching, because with this strategy teachers can know the limits and characteristics of the students. The suggestion is the English teachers also suggested being more creative, developing and varying their strategies in teaching English vocabulary. Keywords:Teachers’ Strategies,English Vocabulary